2018
DOI: 10.3390/nu10070815
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Adherence to a Mediterranean Diet May Not Overcome the Deleterious Effects of Low Physical Fitness on Cardiovascular Disease Risk in Adolescents: A Cross-Sectional Pooled Analysis

Abstract: To examine the combined association of cardiorespiratory fitness (CRF), muscular fitness (MF), and adherence to a Mediterranean diet (MeDiet) on cardiovascular risk in adolescents, a pooled study, including cross-sectional data from two projects [2477 adolescents (1320 girls) aged 12–18 years], was completed. A shuttle run test was used to assess CRF. MF was assessed by the standing-long jump and handgrip tests. Adherence to a MeDiet was assessed by the Kidmed questionnaire. A cardiovascular risk score was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
7
16
0
Order By: Relevance
“…On the other hand, we observed that a greater adherence to the MD is associated with a greater CRF, as also demonstrated other studies [18,23,24]. This fact could be explained to some degree by the above-mentioned relationship with PA, since a higher participation in PA (as a result of active lifestyle) could increase PF level [52].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, we observed that a greater adherence to the MD is associated with a greater CRF, as also demonstrated other studies [18,23,24]. This fact could be explained to some degree by the above-mentioned relationship with PA, since a higher participation in PA (as a result of active lifestyle) could increase PF level [52].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the combination of an optimal adherence to MD, followed by appropriate levels of muscular fitness, seems to provide the highest protection against cardiometabolic risk [21]. Apart from that, it has been found that optimal adherence to the MD could not be enough to prevent some deleterious health effects if adequate levels of muscle strength are not available [24]. These relationships have also been found in the current sample, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…On the other hand, we observed that a greater adherence to the MD is associated with a greater CRF, as also demonstrated other studies [18,23,24]. This fact could be explained to some degree by the abovementioned relationship with PA, since a higher participation in PA (as a result of active lifestyle) could increase PF level [47].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, some studies point out that a combination of high levels of muscle strength and an optimal adherence to MD are associated with healthier metabolic profile [20,21], as well as to a better health-related quality of life [23]. In addition to this, a positive association has been found between adherence to the MD and CRF [18,19,23,24], as well as speed-agility [25], but only in males. Likewise, some studies found positive associations between higher PA level (assessed by the Physical Activity Questionnaire for Older Children [PAQ-C]) and greater adherence to the MD [18,19,22].…”
Section: Introductionmentioning
confidence: 99%